Controlled study of the effect of proprotein convertase subtilisin-kexin type 9 inhibition with evolocumab on lipoprotein(a) particle kinetics. (16th March 2018) - Watts, Gerald F; Chan, Dick C; Somaratne, Ransi; Wasserman, Scott M; Scott, Rob; Marcovina, Santica M; Barrett, P Hugh R
Abstract: Aims: Lipoprotein(a) [Lp(a)], a low-density lipoprotein (LDL) particle covalently bound to apolipoprotein(a) [apo(a)], is a potentially potent heritable risk factor for cardiovascular disease. We investigated the mechanism whereby evolocumab, a monoclonal antibody against proprotein convertase subtilisin-kexin type 9 (PCSK9), lowers Lp(a). Methods and results: We studied the kinetics of Lp(a) particles in 63 healthy men, with plasma apo(a) concentration >5 nmol/L, participating in an 8-week factorial trial of the effects of evolocumab (420 mg every 2 weeks) and atorvastatin (80 mg daily) on lipoprotein metabolism. Lipoprotein(a)-apo(a) kinetics were studied using intravenous D3-leucine administration, mass spectrometry, and compartmental modelling; Lp(a)-apoB kinetics were also determined in 16 subjects randomly selected from the treatment groups. Evolocumab, but not atorvastatin, significantly decreased the plasma pool size of Lp(a)-apo(a) (−36%, P  < 0.001 for main effect). As monotherapy, evolocumab significantly decreased the production of Lp(a)-apo(a) (−36%, P  < 0.001). In contrast, in combination with atorvastatin, evolocumab significantly increased the fractional catabolism of Lp(a)-apo(a) (+59%, P  < 0.001), but had no effect on the production of Lp(a)-apo(a). There was a highly significant association between the changes in the fractional catabolism of Lp(a)-apo(a) and Lp(a)-apoB in the substudy of 16 subjects ( r  = 0.966, P  <   0.001). Conclusions: Evolocumab monotherapy lowered the plasma Lp(a) pool size by decreasing the production of Lp(a) particles. In combination with atorvastatin, evolocumab lowered the plasma Lp(a) pool size by accelerating the catabolism of Lp(a) particles. This dual mechanism may relate to an effect of PCSK9 inhibition on Lp(a)-apo(a) production and to marked up-regulation of LDL receptor activity on Lp(a) holoparticle clearance. Clinical Trial Registration Information: NCT02189837